Improving Quran Memorization Ability on Surah Al-Hujurat Ayat 13 at SDN 027 Cicadas Bandung using Problem Based Learning Model - Sadikin, Achmad; Mahmud, Muhammad Rifqi (Al-Aulad: Journal of Islamic Primary Education, 2023)
This research aims to enhance Quran memorization ability specifically on Surah Al-Hujurat Ayat 13 at SDN 027 Cicadas, Bandung, using the Problem-Based Learning (PBL) model. Classroom Action Research (CAR) method is employed. Results demonstrate improved learning outcomes in both Cycle I and Cycle II. By employing PBL, where students and teachers collaborate as facilitators, memorization skills among fourth-grade students significantly increased. The utilization of varied teaching methods beyond mere discussion enhances students' interest and motivation, leading to better memorization outcomes. The implementation of diverse and engaging teaching methods supports active, innovative, creative, and enjoyable learning (PAIKEM). Analysis reveals a notable improvement in memorization development, increasing from 70% in Cycle I to 87% in Cycle II. The diverse PBL approach tailored to student preferences enhances memorization abilities, supports memory retention, particularly in memorizing short verses like Surah Al-Hujurat.